The conflicted superpower America's collaboration with China and India in global innovation - Kennedy, Andrew (New York Columbia University Press, 2018)
For decades, leadership in technological innovation has sustained U.S. power worldwide. Today, however, processes that undergird innovation increasingly transcend national borders. Cross-border flows of brainpower have reached unprecedented heights, while multinationals invest more and more in high-tech facilities abroad. In this new world, U.S. technological leadership increasingly involves collaboration with other countries. China and India have emerged as particularly prominent partners, most notably as suppliers of intellectual talent to the United States. In The Conflicted Superpower, Andrew Kennedy explores how the world?s most powerful country approaches its growing collaboration with these two rising powers.
Includes bibliographical references and index
Keywords: Globalization -- Political aspects -- United States; Globalization -- Political aspects; International economic relations; United States -- Foreign economic relations -- 21st century; India -- Foreign economic relations -- 21st century; China -- Foreign economic relations -- 21st century